In Vivo and In Vitro Effects of Antituberculosis Treatment on Mycobacterial Interferon-γ T Cell Response - Sauzullo, Ilaria; Mengoni, Fabio; Lichtner, Miriam; Massetti, Anna Paola; Rossi, Raffaella; Iannetta, Marco; Marocco, Raffaella; Borgo, Cosmo Del; Soscia, Fabrizio; Vullo, Vincenzo; Mastroianni, Claudio Maria (PloS one, 2009)
In recent years, the impact of antituberculous treatment on interferon (IFN)-gamma response to Mycobacterium tuberculosis antigens has been widely investigated, but the results have been controversial. The objective of the present study was: i) to evaluate longitudinal changes of IFN-gamma response to M. tuberculosis-specific antigens in TB patients during antituberculous treatment by using the QuantiFERON-TB Gold (QFT-G) assay; ii) to compare the differences in T-cell response after a short or prolonged period of stimulation with mycobacterial antigens; iii) to assess the CD4+ and CD8+ T cells with effector/memory and central/memory phenotype; iv) to investigate the direct in vitro effects of antituberculous drugs on the secretion of IFN-gamma. 38 TB patients was evaluated at baseline and at month 2 and 4 of treatment and at month 6 (treatment completion). 27 (71%) patients had a QFT-G reversion (positive to negative) at the end of therapy, while 11 (29%) TB patients remained QFT-G positive at the end of therapy. Among the 11 patients with persistent positive QFT-G results, six had a complete response to the treatment, while the remaining 5 patients did not have a resolution of the disease. All 27 patients who became QFT-G negative had a complete clinical and microbiological recovery of the TB disease. In these patients the release of IFN-gamma is absent even after a prolonged 6-day incubation with both ESAT-6 and CFP-10 antigens and the percentage of effector/memory T-cells phenotype was markedly lower than subjects with persistent positive QFT-G results. The in vitro study showed that antituberculous drugs did not exert any inhibitory effect on IFN-gamma production within the range of therapeutically achievable concentrations. The present study suggests that the decrease in the M. tuberculosis-specific T cells responses following successful anti-TB therapy may have a clinical value as a supplemental tool for the monitoring of the efficacy of pharmacologic intervention for active TB. In addition, the antituberculous drugs do not have any direct down-regulatory effect on the specific IFN-gamma response.